Dental rehabilitation of patients in the complex treatment of ischemic stroke in the acute period. Part 2 (LLC "Endo Press", 2020)
Cerebrovascular accidents due to the high prevalence and serious consequences for the health of the population represents an important medical and social problem. The purpose of the work was to determine the clinical significance of diseases of dental system and how best dental care in the acute phase of stroke. Our study revealed that dental intervention in acute stroke are safe subject to the positive dynamics in the condition of patients and carrying out preventive measures.